How Pro-Active Police Synergy Program Can Improve the Police Professionalism in Indonesia? - Kurniawan, Rudy Cahya (Law Research Review Quarterly, 2023)
Professionalism is a pivotal strategy for advancing organizational efficacy, particularly within institutions like the Police. This analysis employs a descriptive approach to delve into the Republic of Indonesia's Police strategy for augmenting professionalism, primarily achieved by bolstering inter-agency collaboration and fortifying human resources. This approach aligns with the overarching goals outlined in the National Police's Grand Strategy, emphasizing the augmentation of both the quality and quantity of personnel. The concerted effort to enhance professionalism is substantiated by a commitment to allocate sufficient budgetary resources and provide state-of-the-art facilities and infrastructure. The multifaceted strategy hinges on cultivating a robust synergy within the police force, recognizing that optimal performance and the conduct of its members are intertwined. The efficacy of this professionalism-centric approach is contingent upon various factors, with government backing playing a pivotal role. Support from the government serves as a catalyst for the Police's endeavors, ensuring that the strategy is seamlessly integrated into broader national objectives. Additionally, the revitalization of the National Police further reinforces their commitment to professionalism, manifesting in comprehensive reforms and structural improvements. As the Indonesian National Police navigates this path, the interconnected dynamics of government support and internal revitalization form the linchpin for fostering a culture of professionalism within the organization, thus contributing to overall organizational excellence.